Study on the determinants that influence the fluctuation in the world price of rubber / Nur Hafizakhtar Zainol Abidin (Faculty of Business and Management, 2007)
The fluctuation of natural rubber price has raise major concern among the industry player and the consumer itself. The instability in the price of natural rubber last few years is influence by several factors. Natural rubber is a vitally important source of commodity for all sectors of the economy in the world. There are several factors that influence the price of natural rubber; the crude oil price, synthetics rubber price, consumption and production of natural rubber. The purpose of this study is to verify the factors that influence the price of the natural rubber. Furthermore, it is also conduct in order to identify the effect of the factors to the price of the natural rubber. The study is intended to explore the solutions for the volatile price of natural rubber. This study will be using descriptive research design. Moreover, the study will be using secondary data instead of primary data. Secondary data will be used due to the difficulty in gathering primary data. The study will be using internet, newspaper, magazines and past research in understanding the natural rubber prices. The study is done in order to find the determinants that influence the fluctuations in the world price of rubber. Beside that, the study is also expected to explain the trend that occurs in world price of natural rubber from year 2004 until 2006.